Challenges teaching ESP vocabulary to engineering students (Global Scientific Review, 2022)
This article provide general overview and course design of English for Specific Purposes in the field of ELT, the difficulties related teaching ESP engineering students and effective strategies for teaching special vocabulary for engineering students. Teaching and learning vocabulary is crucial in language acquisition and it has been in the central attention of most English teachers for the last decades. In order to develop communicative competence of language learners, teachers should encourage them to learn as many words as possible. As the world has been becoming a global village, there are appeared huge demand for English for specific purposes (ESP) courses. There are diverse courses such as business English, scientific English, technical English, English for medical professionals , English for waitress and English for engineers. Mainly these courses are differentiated with its content as well as special vocabulary of target field. There may be appear possible challenges for teachers as well as for learners related to vocabulary as special words used only in narrow field. Hence there are some effective strategies to overcome those difficulties which are illustrated below.